EFEITO DO TRATAMENTO QUÍMICO NA SANIDADE DE SEMENTES DE ESPÉCIES FLORESTAIS - Silva, Lilianne Gomes Da; Cosmi, Fernando Carrara; Jesus, Waldir Cintra De; Souza, Antônio Fernando De; Moraes, Willian Bucker [UNESP] (Universidade Federal de Santa Maria, 2011)
This study evaluated the effect of different fungicide and sodium hypochlorite treatments in reducing the incidence of fungi on seeds of native species of the Atlantic rainforest. The experiment was done using the completely randomized design in a 5x5 factorial with five levels of factor A (forest species) and five levels of factor B (chemical treatment and surface disinfection with sodium hypochlorite) with four replications. The fungal genera Fusarium, Alternaria, Aspergillus and Penicillium were identified. The species ‘Jacarandá- da-Bahia’ and ‘Ipê-roxo’ had lower fungal incidence, 1.0% and 1.3%, respectively. Except for ‘Angico Vermelho’, the fungicide pencycurom and sodium hypochlorite were not significantly different from the control in the species evaluated. Seed treatment with fungicides ‘Captan’ and ‘Tiram’ yielded satisfactory results in reducing the incidence of fungal contamination in forest species seeds.

O presente trabalho teve como objetivo avaliar o efeito de diferentes tratamentos com fungicidas e hipoclorito de sódio na redução da incidência de fungos em sementes de espécies florestais nativas da Mata Atlântica. O experimento foi conduzido empregando-se o delineamento inteiramente casualizado, no esquema fatorial 5x5, com cinco níveis do fator A (espécies florestais) e cinco níveis do fator B (tratamento químico e desinfestação superficial com hipoclorito de sódio), com quatro repetições. Foram identificados os gêneros fúngicos Fusarium, Alternaria, Aspergillus e Penicillium. As espécies de jacarandá-da-Bahia e ipê-roxo apresentaram menor incidência fúngica com 1% e 1,3%, respectivamente. Exceto para a espécie de angico- vermelho, o fungicida Pencicurom e o hipoclorito de sódio não deferiram estatisticamente da testemunha nas espécies avaliadas. Os tratamentos de sementes com os fungicidas Captan e Tiram proporcionaram resultados satisfatórios quanto à redução da incidência fúngica em sementes de espécies florestais.
EFFECT OF CHEMICAL CONTROL ON THE SANITY OF FOREST SPECIES SEEDS
Keywords: fungicide treatment; sodium hypochlorite; seed pathology; fungicidas; hipoclorito de sódio; patologia de sementes